(untitled) (Acta Scientiarum. Health Sciences, 2018)
In Brazil, a large part of the population of elderly people living in rural areas have difficult access to specialized health services. The objective of this study was to evaluate the association between self-reported of osteo-articular pain with functional and clinical indicators on elderly residents in riparian Maués-AM. Was conducted a cross-sectional study, observational who initially estimated the prevalence of osteo-articular pain through self-reporting of the elderly. The elderly the study were selected from families registered in the family health strategy. The questions were applied in the form of a structured interview. Most of the sample was constituted by men, with a prevalence of 64.2% (n = 1159) of seniors who reported some form of osteo-articular pain, being similar among elderly residents in urban region and in Riverside-rural region. Older women were more involved and the elderly over 75 years of age. The elderly with osteo-articular pain showed a significantly higher prevalence of morbidities and considered bad to your health and life. It is necessary to promote public policies for the implementation of programs that target the prevention and control of musculoskeletal diseases. To be able to promote a better functional ability and quality of life for this population.